Finite element analysis of stress distribution in unilateral distal extension partial dentures: a comparison of four attachment designs - Maha Nagy Mohamed Kamal; Haitham Amr Mohammed; Abdallah Shokry (BMC Oral Health)
Abstract Background Due to lack of consensus on optimal unilateral attachment retained partial denture design, this finite element comparative analysis study was conducted to measure the stresses induced from four different attachment-retained lower Kennedy class II removable partial denture (RPD) designs around the abutment teeth and the supporting residual ridge. Materials and methods An educational cast of lower Kennedy class II having the first premolar as the last standing abutment was used. The abutment teeth - canine and first premolar- of the edentulous side were reduced to receive two splinted porcelain veneered metal crowns, while the intact side was prepared to receive a double Aker’s clasp and mesial rest seat for indirect retention. Then the cast was scanned, and the partial denture components and the splinted crowns were designed and assembled digitally using Blender4dental software. According to the attachment used; partial dentures were designed as follows: design 1: unilateral PD retained by OT cap attachment, design 2: unilateral RPD retained by double OT cap attachment, design 3: unilateral RPD retained by mini-bar attachment, and design 4: RPD retained by OT cap with major connector crossing the arch for stabilization (conventional RPD). The Meshmex software was used to modify the STL file, and the Abaqus software was used for finite element analysis. On the edentulous side, the first and second molars were subjected to vertical loads of 200 N and tangential loads of 23.5 N, while the first and second premolars were subjected to vertical loads of 140 N and tangential loads of 16.45 N. The von Misses stress levels induced around the abutments and at the residual ridge were measured and compared. Results The lowest stresses were found with the conventional RPD design. Regarding von Mises stresses on the prepared abutments; The lowest von Mises stresses were found in design 4, followed by design 1, then design 3, while the highest von Mises stresses were found in design 2. Regarding von-Mises stresses on the residual ridge, the lowest Von Mises stresses were found in design 4, followed by design 3, then design 2, while the highest Von Mises stresses were found in design 1. Conclusions The attachment retained RPD with a conventional design offered the lowest stresses applied for the abutment and the residual ridge. OT cap attachment exerts the least stress on the abutments when used in unilateral design RPD, so it is preferable for abutment preservation but contraindicated in weak ridges, however, the double OT cap exerts the highest amount of force on the abutment teeth and could be used with abutments showing perfect periodontal condition.